Wilenska powiesc kryminalna - Romanowska, Felicja; Mackiewicz, Jozef; Wyszomirski, Jerzy; Mackiewicz, Stanislaw, 1896-1966.; Charkiewicz, Walerian (London : Kontra, 1995)
A satire on the culture and intellectual life in Vilnius, written in the guise of a detective story.
Written under a pseudonym by: Jerzy Wyszomirski, Walerian Charkiewicz, Josef Mackiewicz and Stanislaw Mackiewicz